H. Wendl Leaf Metabolites Potentiate the Radiosensitivity of Hepatocellular Carcinoma Through Ki67 and PARP Inhibition - Nabil M. Selim PhD; Seham S. El-Hawary PhD; Soheir M. El Zalabani PhD; Rehab Nabil Shamma PhD; Nariman El Sayed Mahdy PhD; Noheir H. Sherif PhD; Khayrya A. Youssif PhD; Usama Ramadan Abdelmohsen PhD; Mai H. Mekkawy PhD; Hanan A. Fahmy PhD (Integrative Cancer Therapies)
Objectives: Hepatocellular carcinoma (HCC) represents the third-most prevalent cancer in humans worldwide. The current study’s objective is to search for the potentiality of Washingtonia robusta H. Wendl ( W. robusta ) leaf extract in a nanoemulsion (NE) form in enhancing radiotherapy against HCC induced in rats using diethylnitrosamine (DEN). Material and methods: The metabolic composition of the bioactive extract of W. robusta leaves was investigated by LC-MS. Oral epithelial (OEC) and liver carcinoma (HepG2) cell lines were used to examine the safety and anticancer activity of the NE, respectively. In the in vivo study, HCC was induced in male albino rats through administration of DEN in drinking water for 8 weeks, then treatment with NE (100 mg/kg) until the experiment’s ending. Rats were irradiated by a fractionated dose of 2Gy*4. Results: NE exerted remarkable cytotoxicity in comparison to the parent extract and the standard doxorubicin on the HepG2 cell line. Besides, the NE administration and/or γ-irradiation (IRR) significantly reduced the elevated alanine aminotransferase (ALT), total proteins, and albumin levels in HCC-induced rats. Likewise, the tumor markers alpha-fetoprotein (AFP) and gamma-glutamyl transferase (GGT) levels were considerably reduced in HCC rats. In addition, NE treatment before IRR significantly decreased the expression of the poly ADP ribose polymerase-1 ( PARP1) enzyme and Ki67. Furthermore, the histological investigations strongly confirmed the combined effect of NE and IRR in fighting DEN-induced HCC. Conclusion: NE of W. robusta extract may possess a radiosensitizing novel impact and provide a new strategy to combat HCC in clinical practices.